The Relationship between Islamic Education and Global Ethics in Building Humanistic Awareness in the Post Truth Era - Syaban Abdul Karim (Spiritus: Religious Studies and Education Journal, 2024)
In a post-truth era marked by disinformation and mistrust of facts, it is important to consider the role of Islamic education and global ethics in building a humanistic awareness. Both have the potential to be drivers in overcoming the growing crisis of confidence and social polarization. This research explores the relationship between Islamic education and global ethics in the context of strengthening humanistic awareness. Through analysis of literature and case studies, the study highlights the importance of integrating humanist values, such as tolerance, justice, and empathy, into the curriculum of Islamic education. Moreover, a critical and reflective approach to disinformation as well as an emphasis on cross-cultural and religious understanding in a global ethical context are also identified as key factors in promoting humanistic awareness. The results of this research offer new insights into how global Islamic education and ethics can work together to produce individuals who are more aware of human values in the face of the challenges of the post-truth era. In conclusion, close collaboration between Islamic education and global ethics can help build a strong foundation of humanistic consciousness for a more inclusive and harmonious society in the future.